WHAT CAN CAUSE CUSTOMERS SHOP ONLINE FOR IMPORTED GOODS POST-ENACTMENT REGULATION OF FINANCE MINISTER CONCERNING CUSTOMS, EXCISE AND TAX PROVISIONS ON IMPORTED SHIPMENTS? - Prasaja, Disma; Fatmasari, Fajria; Fatmawati, Inayatullah (Dinasti Publisher, 2022)
This study aimed to analyze the determinants of online shopping decisions for goods from abroad after the enactment of Regulation of Finace Minister number 199 year of 2019 regarding customs, excise and tax provisions on imported shipments. Foreign goods purchased for more than USD 3 will be taxed so that the existence of this provision will result in the price of goods becoming more expensive. This research will identify factors that can shape shopping decisions by Indonesian consumers. The population in this study is market place consumers who have made transactions of imported goods or purchases through the marketplace. The number of samples used as many as 30 respondents based on the number of indicators with an error rate of 5%. The survey was conducted using an online questionnaire and processed using a data processing application. Based on the results of data analysis, this study resulted in 5 new factors, namely Product Quality, Physical Factors, Shopping Value, Service Quality, Platform, and Subjective Norms. The most dominant factor among these factors is product quality.